2020
DOI: 10.1111/cea.13750
|View full text |Cite
|
Sign up to set email alerts
|

Association between childhood asthma and attention deficit hyperactivity or autism spectrum disorders: A systematic review with meta‐analysis

Abstract: Background: Children with asthma are at risk of depression and anxiety and growing evidence suggest they may also be at risk of attention deficit hyperreactivity disorder (ADHD) and autism spectrum disorder (ASD). Here, we conducted a systematic review with meta-analysis of studies investigating association between asthma and ADHD or ASD in children. Methods: A comprehensive search using PubMed, EMBASE and Cochrane Library databases was completed in March 2019. Observational human studies published in English,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 66 publications
3
29
0
Order By: Relevance
“…Previous studies examining the association between allergic conditions and ADHD are predominately focused on respiratory allergy and skin allergy [ 17 , 18 ]. For example, a meta-analysis including 25 studies about asthma and ADHD found a significant association between asthma and ADHD, with an odds ratio of 1.52 [ 19 ]. Hospital-diagnosed atopic dermatitis was found to be associated with ADHD in a case-control study in Danish children [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies examining the association between allergic conditions and ADHD are predominately focused on respiratory allergy and skin allergy [ 17 , 18 ]. For example, a meta-analysis including 25 studies about asthma and ADHD found a significant association between asthma and ADHD, with an odds ratio of 1.52 [ 19 ]. Hospital-diagnosed atopic dermatitis was found to be associated with ADHD in a case-control study in Danish children [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal maternal immune activation is posited to be one mechanism underlying the relationship between maternal and offspring asthma (Barrett, 2008). Children with asthma have been reported to have more difficulties with cognitive capabilities (e.g., executive functioning; Irani et al, 2017) and behaviour (e.g., attention-deficit/hyperactivity disorder; Kaas et al, 2021). There is also some evidence that children with asthma differ in temperament from the general population (Kim et al, 1980;Lilljeqvist et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Asthma had a signi cant association only with the severity of total ADHD symptoms. Considering that previous studies have reported that children with asthma had an increased risk of developing severe ADHD symptoms 18,21,35 , this result may be attributed to the small number of included studies (n = 3). The results of the subgroup analysis of different types of atopic diseases indicated that all atopic diseases were signi cantly associated with the severity of total ADHD symptoms; however, inconsistent heterogeneity was observed in the association between atopic diseases and the severity of hyperactivity/impulsivity and inattention.…”
Section: Discussionmentioning
confidence: 88%
“…A previous study investigated the relationship between atopic diseases and ADHD 15 . A higher risk of ADHD was noted in patients with all three atopic diseases, namely atopic dermatitis, asthma, and atopic rhinitis (i.e., atopic march) 16,17 . In addition, children with both atopic diseases and ADHD had an increased risk of developing more severe ADHD symptoms compared with those with only ADHD 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation